Association of Municipal Engineers seminar on green waste recycling what next? : speakers' papers. (Institution of Civil Engineers, 1992)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a seminar held on 12 November 1992.
Keywords: Organic wastes -- Recycling -- Congresses.; elektronické knihy; electronic books